2010
DOI: 10.1074/jbc.m109.092536
|View full text |Cite
|
Sign up to set email alerts
|

Dual Binding Mode of the Nascent Polypeptide-associated Complex Reveals a Novel Universal Adapter Site on the Ribosome

Abstract: Nascent polypeptide-associated complex (NAC) was identified in eukaryotes as the first cytosolic factor that contacts the nascent polypeptide chain emerging from the ribosome. NAC is present as a homodimer in archaea and as a highly conserved heterodimer in eukaryotes. Mutations in NAC cause severe embryonically lethal phenotypes in mice, Drosophila melanogaster, and Caenorhabditis elegans. In the yeast Saccharomyces cerevisiae NAC is quantitatively associated with ribosomes. Here we show that NAC contacts sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 47 publications
7
62
0
Order By: Relevance
“…However, different models suggest that SRP function is influenced by NAC and that this dynamic interplay is important for protein targeting to the ER (Zhang et al, 2012). Also, NAC has been shown to bind uL23 (Wegrzyn et al, 2006), although other studies identified eL31 as the major ribosomal binding site of NAC (Pech et al, 2010; Zhang et al, 2012). Therefore, it would be interesting to see if and how NatA may be involved in this process and what the consequences are for the acetylation status of proteins.…”
Section: Nata In Other Organismsmentioning
confidence: 99%
“…However, different models suggest that SRP function is influenced by NAC and that this dynamic interplay is important for protein targeting to the ER (Zhang et al, 2012). Also, NAC has been shown to bind uL23 (Wegrzyn et al, 2006), although other studies identified eL31 as the major ribosomal binding site of NAC (Pech et al, 2010; Zhang et al, 2012). Therefore, it would be interesting to see if and how NatA may be involved in this process and what the consequences are for the acetylation status of proteins.…”
Section: Nata In Other Organismsmentioning
confidence: 99%
“…The NAC is a heterodimeric complex that associates with ribosomes near the polypeptide exit tunnel. 31 Although the function of the NAC is poorly defined, it is thought to have roles in co-translational protein folding 32 and in protein targeting to mitochondria 33 and the endoplasmic reticulum. 34 The RAC consists of the Heat Shock Protein (Hsp) 70/40 pair Ssz1/ Zuo1, 35 which is anchored to the ribosome in close proximity to the polypeptide exit tunnel via a charged C-terminal region of Zuo1.…”
Section: Introductionmentioning
confidence: 99%
“…NAC transiently associates with the large ribosomal subunit close to the peptide tunnel exit and binds a broad spectrum of ribosome-nascent chain complexes (RNCs) ( 3). In vitro NAC association sterically prevents indiscriminate binding of RNCs to the ER membrane, regardless of whether the nascent chain has a signal sequence or not ( 4,5). Addition of SRP, however, specifically rescues ER targeting of signal-containing RNCs ( 6).…”
mentioning
confidence: 95%
“…Finally, Gamerdinger et ( 4), and that NAC binds translating ribosomes, unless an emerging signal sequence provides a selective binding advantage to SRP. Other in vitro data suggest that there is an alternative NAC ribosome binding site near eL31 ( 5,12), and that both NAC and SRP concomitantly bind the ribosome ( 12). SRP could quickly scan translating ribosomes irrespective of NAC presence, until an emerging signal sequence triggers strong SRP binding and NAC release.…”
mentioning
confidence: 97%
See 1 more Smart Citation